(3JbjjO aj PcQ TQaGA GdeZQH hUdMGFg hbHGFdgs - (3YHO GdYXje GdRehQjs
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdHbGA hGdceGd hdfHOC HJbOje ehdGfG EOQjS , ZP gh TeS Cgd GdeZQH (B( (3QV (B) (3PcQ ehdGfG EOQjS GdPi CJi ef GdeTQb Edi GdeZQH bOe Edjg gh hCNhg ehdGfG SdjeGf GdfGRd HJdeSGf s
(3BNQgG (B:s
(3hCeG ChdGO GdMGL aCUdge ef GdeTQb , hge Ydi aQbJjf hCeG GdMjGfjI aefge aQbI ChdGO YeQGf hENhGfge ai OcGdI hChdGO YdjGf hENhGfge ai GdQMGefI , hGdHGbi ef PQjI LGdhJ hENhGfge HMhR eQGcT GfJgi HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag ai GdKGfi ef QHjY GdBNQ YGe (B1324s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B29s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs